Severe Ventral Erosion of Penis Caused by Indwelling Urethral Catheter and Inflation of Foley Balloon in Urethra—Need to Create List of “Never Events in Spinal Cord Injury” in order to Prevent These Complications from Happening in Paraplegic and Tetraplegic Patients - Subramanian Vaidyanathan; Bakul M. Soni; Peter L. Hughes; Gurpreet Singh; Tun Oo (Advances in Urology)
Never Events are serious, largely preventable patient safety incidents that should not occur if the available preventative measures have been implemented. We propose that a list of “Never Events” is created for spinal cord injury patients in order to improve the quality of care. To begin with, following two preventable complications related to management of neuropathic bladder may be included in this list of “Never Events.” (i) Severe ventral erosion of glans penis and penile shaft caused by indwelling urethral catheter; (ii) incorrect placement of a Foley catheter leading to inflation of Foley balloon in urethra. If a Never Event occurs, health professionals should report the incident through hospital risk management system to National Patient Safety Agency's Reporting and Learning System, communicate with the patient, family, and their carer as soon as possible about the incident, undertake a comprehensive root cause analysis of what went wrong, how, and why, and implement the changes that have been identified and agreed following the root cause analysis.